The Use of Digital Flashcard in Teaching Vocabulary Mastery - Nurjanah, Intan; Nugroho, Kurniawan Yudhi (IKIP Siliwangi, 2025)
This study examines how well digital flashcards can improve elementary school students vocabulary mastery, with a particular emphasis on number vocabulary. A fourth-grade classroom in Semarang Regency, Central Java, Indonesia, served as the study’s site because it was recognised that many students lacked adequate vocabulary skills. To gauge vocabulary growth, the study used a pre-test and post-test as part of a pre-experimental design and quantitative methodology. With the pre-test mean at 60.83 and the post-test mean increasing to 82.22 following the intervention, the results showed a significant improvement in the students’ scores. The Statistical Package for the Social Sciences (SPSS) was used to analyse the data. The paired t-test revealed a significant increase in vocabulary mastery, with a p-value of 0.000, below the 0.05 cutoff. As a result, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted, demonstrating the efficacy of digital flashcard in improving vocabulary acquisition. Based on the results, digital flashcard can be a useful teaching tool that can be used in a variety of ways and offer young learners an engaging and interactive learning experience.